1991
DOI: 10.1002/mar.4220080303
|View full text |Cite
|
Sign up to set email alerts
|

Origin of rumor and tone of message in rumor quelling strategies

Abstract: Past studies have shown that, while refuting rumors, certain strategies, such as the introduction of a stimulus that deflects allegation, are superior to mere refutation. In this study, the originator of a rumor and the tone of a refutational message are proposed as factors that influence the success of rumor quelling strategies. It is shown that no refutation is superior when the originator is a negative stakeholder, whereas other types of refutation are more effective when the stakeholders are neutral or pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Bordia, DiFonzo, and Schulz (2000) showed refutation to be effective in reducing belief in the rumor that the undergraduate library was going to close down when its source was perceived as high on both honesty and appropriateness. In another study by Iyer and Debevec (1991), a vigorous and active refutation was an effective strategy to counter a rumor that had originated from a credible source.…”
mentioning
confidence: 99%
“…Bordia, DiFonzo, and Schulz (2000) showed refutation to be effective in reducing belief in the rumor that the undergraduate library was going to close down when its source was perceived as high on both honesty and appropriateness. In another study by Iyer and Debevec (1991), a vigorous and active refutation was an effective strategy to counter a rumor that had originated from a credible source.…”
mentioning
confidence: 99%
“…Vigorous refutations of rumors may be most effective when the source of the rumor or disinformation is portrayed as having something to gain from the rumor and when those doing the refuting end their message on a conciliatory note (Iyer and Debevec, 1991). As for how best to transmit these refutations, U.S. sources on the ground in Iraq have argued that face-toface rumor control is much more effective than print or radio efforts (Steele, 2003).…”
Section: Methods Of Responsementioning
confidence: 99%
“…In context of rumor communication, past studies have revealed that verifying information and rebutting false rumors which is a core behavior of accuracy-aimed information seeking (Leeper and Slothuus, 2014), make people have critical thoughts (e.g., Allport and Postman, 1947;Bordia et al, 2000;Iyer and Debevec, 1991), which could ultimately curb the negative impact of false rumors (Tanaka et al, 2012). Therefore, seeking information with accuracy in mind is essential in minimizing the circulation of false rumors.…”
Section: Accuracy-oriented Information Seeking and An Informed Publicmentioning
confidence: 99%